Digital migrants and digital diaspora: new problems and trends of international migration - Yu. G. Volkov; V. V. Krivopuskov; V. I. Kurbatov (Цифровая социология)
The “Digital migrant”, as a concept, is used to refer to a migrant who realises his information needs by information digital technologies. This give rise to new trends in international migration processes, among which the global informatisation can be highlighted. This is expressed in the mass representation of migrants in social networks, in virtual network migrant communities’ creation. The digital diaspora being an electronic platform is the basis for migrants’ access to online public content, serves as an information base for the migrants’ digital adaptation and their virtual identity’s formation, which is becoming more and more transnational.The article proposes an instrumental definition of “digital migrant” concept, reveals factors of digital ethnic national community’s functioning, features of migrants’ social adaptation in digital diaspora, new types of interpersonal communication in digital diaspora, new trends and problems of digital migration, and new types of migrants’ identity and of digital virtual identity